Impact of Wellness Program to Employee Retention at Bestlink College of the Philippines, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Employee retention is the most common problem of every organization. Retention is themost important aspect of every organization that can be improved by introducing variants ofactivities and programs to make them feel valuable and included. The best program tointroduce in the organization to make the retention rate decrease is a wellness program thatcan track the needs of the employees. This can include stress management and makingresources about mental health available. And add activities that will improve both physicaland mental health. This step can lead to better performers and well-motivated employeesthat can lead to success.The result shows that the wellness practices observed by the respondents at Bestlink weremostly about health and lifestyle events, with 29 or 58%. The four (4) variables in the parts ofwhat could be the impact of wellness programs on employee retention are all interpreted asextremely aware with their respective means of commitment (3.24), performance (3.35),mental health (3.24), and physical health (3.24). What are the problems encountered inwellness programs that get 13 or 26% out of 50?The study shows that most of the respondents were female and currently employed atBestlink. Most of the respondents were non-teaching and had 1 - 2 years in service. It alsoreveals that wellness programs can improve employee retention in terms of commitment,performance, mental health, and physical health, and the common problem that may beencountered by the response of respondents is that it thinks that it can add expense to theorganization. The researchers also suggested improving the wellness program by keepingthe most needed of the employees and keeping the program aligned to make employeesperform better and motivated. At the end of the study, the researchers providerecommendations, activities, and steps to enhance and improve employee retention in theorganization by implementing wellness programs.
Keywords: Business Administration